2021
DOI: 10.1038/s41698-021-00156-5
|View full text |Cite
|
Sign up to set email alerts
|

Swiss-PO: a new tool to analyze the impact of mutations on protein three-dimensional structures for precision oncology

Abstract: Swiss-PO is a new web tool to map gene mutations on the 3D structure of corresponding proteins and to intuitively assess the structural implications of protein variants for precision oncology. Swiss-PO is constructed around a manually curated database of 3D structures, variant annotations, and sequence alignments, for a list of 50 genes taken from the Ion AmpliSeq TM Custom Cancer Hotspot Panel. The website was designed to guide users in the choice of the most appropriate structure to analyze regarding the mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Following our subsequent investigations, it was found that “17:7674220_C > T” SNV, which is regarded as a “hotspot mutation” in the literature, is an arginine to glutamine single nucleotide substitution occurring at 248th residue of TP53 ( Shajani-Yi et al, 2018 ). We also explored the location of the identified mutation “17:7674220_C > T” (R248) in the three-dimentional structure of TP53 protein using the web service Swiss-PO ( Krebs et al, 2021 ). The structure is shown in Supplementary Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
“…Following our subsequent investigations, it was found that “17:7674220_C > T” SNV, which is regarded as a “hotspot mutation” in the literature, is an arginine to glutamine single nucleotide substitution occurring at 248th residue of TP53 ( Shajani-Yi et al, 2018 ). We also explored the location of the identified mutation “17:7674220_C > T” (R248) in the three-dimentional structure of TP53 protein using the web service Swiss-PO ( Krebs et al, 2021 ). The structure is shown in Supplementary Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
“…The problem of predicting mutation's effect on protein structure and function is well studied in the literature with a scope ranging from predicting mutation effect from protein sequence [15,16,17] to 3D mapping of mutations onto protein structures with visualization and highlighting their impact [18,19]. However, the specific impact of missense mutations in the binding site on protein-ligand binding affinity is much less covered.…”
Section: Related Workmentioning
confidence: 99%
“…This general workflow can be integrated or complemented with tools to predict the functional impact of the identified mutations [46], resources to map the mutations on the 3D structure of a given protein [47][48][49][50][51], software that align the 3D structures instead of linear amino acid sequences [52], methods to visualize the position of the mutations in single proteins or the analysis of co-occurrence and mutual exclusivity of mutations [53]. Altogether this workflow defines a 'domain-based mutation prioritization'.…”
Section: Domain-based Approaches For the Identification Of Mutation Hotspotsmentioning
confidence: 99%